2017
DOI: 10.12816/0042245
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Coma Scale in Anticipation of Sepsis and Septic Shock : Review Article

Abstract: Evaluation of level of consciousness has become essential for anticipation of sepsis and septic shock. Both the Sequential Organ Failure Assessment (SOFA) score and the quick SOFA score utilize the Glasgow Coma Score (GCS) for screening of sepsis. Objectives: the aim of this review is to determine and study the role of Glasgow coma score in anticipation of sepsis and septic shock. Methods: To achieve this aim, we have searched online database, namely PubMed and Cochrane Library for studies and review articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…2,11,21 In contrast to a French study 21 and a multinational study 11 which found older age (age ≥65 years) to be a significant risk factor for SS-related mortality, it was observed in this study that being an infant was instead a risk factor, probably explained by the immature immunity of infants. 26 Similar to previous studies, [27][28][29] a low GCS was found in this study to be associated with mortality in patients with SS. It is noteworthy that a low GCS is also a reliable indicator of sepsis through the SOFA or quick SOFA score assessment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2,11,21 In contrast to a French study 21 and a multinational study 11 which found older age (age ≥65 years) to be a significant risk factor for SS-related mortality, it was observed in this study that being an infant was instead a risk factor, probably explained by the immature immunity of infants. 26 Similar to previous studies, [27][28][29] a low GCS was found in this study to be associated with mortality in patients with SS. It is noteworthy that a low GCS is also a reliable indicator of sepsis through the SOFA or quick SOFA score assessment.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that a low GCS is also a reliable indicator of sepsis through the SOFA or quick SOFA score assessment. 18,27 Eidelman et al 29 found that SS patients with a GCS of 15, 14 to 13, 12 to 9, or 8 to 3 had mortality rates of 16%, 20%, 50%, and 63%, respectively. However, the various levels of GCS and associated mortality in the current series were not stratified.…”
Section: Discussionmentioning
confidence: 99%
“…These assess the degree of respiratory, renal, cardiovascular, neurological, hepatic, and hematological impairment, and qSOFA is used in the emergency department for faster organ failure scoring, taking into account respiratory rate, hypotension, and the Glasgow coma score [ 48 , 49 ]. Higher mortality rates have been reported in patients with GCSs <15, as well as neurological impairment in 25–33% of patients with sepsis [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This comparably studies made by Alalawi et al that GCS score not only predicts development of sepsis but also has prognostic value. Patients who have low GCS have a high mortality rate [13].…”
Section: Discussionmentioning
confidence: 99%